ADOPTION OF E-COMMERCE PLATFORMS AMONG KASHMIRI ENTREPRENEURS: TRENDS AND CHALLENGES - Amir Arshid; Asif Bashir (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This treatise delves into the burgeoning adoption of e-commerce platforms by Kashmiri entrepreneurs, examining the intricate dynamics underpinning this digital transformation. The study illuminates the duality of e-commerce as both an opportunity and a challenge within the unique socio-economic and geopolitical context of Kashmir. Entrepreneurs entrenched in traditional sectors such as handicrafts, horticulture, and tourism are increasingly leveraging digital platforms to amplify market access, mitigate operational expenditures, and diversify revenue streams. Despite these advancements, the region grapples with formidable impediments, including precarious internet infrastructure, pervasive digital illiteracy, and a deficit of trust in online transactions. Employing a mixed-methods approach, this inquiry amalgamates quantitative data from structured surveys and qualitative insights from semi-structured interviews, encompassing a diverse cohort of entrepreneurs. The findings elucidate critical enablers of e-commerce proliferation, such as the advent of localized platforms, the ascendancy of social media as a marketing conduit, and governmental interventions fostering digital entrepreneurship. Concurrently, the research underscores persistent barriers, including logistical conundrums, cybersecurity vulnerabilities, and sociocultural constraints, particularly affecting women entrepreneurs. The study posits that a synergistic approach encompassing infrastructural enhancement, capacity-building initiatives, and tailored policy frameworks is imperative to galvanize the e-commerce ecosystem in Kashmir. By addressing these structural challenges, e-commerce could metamorphose the region’s economic paradigm, fostering resilience and empowering marginalized demographics. This paper, thus, contributes to the discourse on digital inclusivity and sustainable entrepreneurship in developing territories, presenting a compelling case for the transformative potential of digital commerce.